2016
DOI: 10.7759/cureus.786
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Undergraduate Major and Housing with Depression in Undergraduate Students

Abstract: Introduction: Past literature has shown that college undergraduates are particularly vulnerable to depression. The objective of this study is to find if certain majors and housing arrangements are associated with major depression as assessed by the Patient Health Questionnaire (PHQ-9), after adjustment for age, gender, and family history of depression.Methods: Participants were undergraduates at a large public university that used the university health center from April 1 - November 4, 2013. Participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The art faculty may have more depressive symptoms attributed to factors associated with the stress of college life, financial problems, and the uncertainties of future careers associated with this chosen faculty. 47 Students who consumed energy drinks had a higher mean depression score than those who did not; one study found a relationship between the frequency of energy drink consumption and depression, but the study does not ensure the cause-result relationship. 48 Another study held over two years to investigate the effects of energy drink consumption on depression found an increase in depression among male participants.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The art faculty may have more depressive symptoms attributed to factors associated with the stress of college life, financial problems, and the uncertainties of future careers associated with this chosen faculty. 47 Students who consumed energy drinks had a higher mean depression score than those who did not; one study found a relationship between the frequency of energy drink consumption and depression, but the study does not ensure the cause-result relationship. 48 Another study held over two years to investigate the effects of energy drink consumption on depression found an increase in depression among male participants.…”
Section: Discussionmentioning
confidence: 96%
“…The art faculty may have more depressive symptoms attributed to factors associated with the stress of college life, financial problems, and the uncertainties of future careers associated with this chosen faculty. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Students enrolling in engineering major had a higher risk of developing MDS than students from other majors. The relationship between depression and academic major remains inconclusive and we argue that the severity of depression could associate with the characteristics and culture of the university and discipline [ 41 , 42 ]. Our study sample matriculated to a university where engineering is a prestigious and competitive major.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that art majors used both the Internet and Facebook more than science majors. There is some evidence to suggest that students in arts and humanities fields experience more depressive and anxiety symptoms than students in science [57][58][59] . One explanation for this could be that sometimes students settle on art as their major because they cannot meet the more rigorous academic requirements of a science major 59 .…”
Section: Discussionmentioning
confidence: 99%